Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Berkat Mahkota Putra Kota Tangerang Selatan - Prasanti Prasanti; Komala, Laura (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
employee performance partially or simultaneously at PT Berkat Mahkota Putra South Tangerang. This research method uses a quantitative method. The population in this study were employees of PT Berkat Mahkota Putra Tangerang Selatan with a total of 70 people. This data collection technique was carried out by taking objects from the sample or can be called sampling, the sampling method using the saturated sample technique. the research sample was 70 respondents. Data analysis and testing techniques include validity tests and reliability tests, classical assumption tests, statistical tests including simple & multiple linear regression tests, determination coefficient tests, correlation coefficient tests and hypothesis tests. From the results of this study, the first hypothesis test, namely the effect of work motivation (X1) on employee performance at PT. Berkat Mahkota Putra Tangerang Selatan obtained t_count> t_table or (10.848> 1.668) this is reinforced by the sig value (0.000 <0.05). Thus, H_O is rejected and H_1 is accepted. So it can be stated partially that there is a significant influence on employee performance (Y) at PT. Berkat Mahkota Putra Tangerang Selatan. While the second hypothesis test, namely the influence of Work Discipline (X2) on employee performance at PT. Berkat Mahkota Putra Tangerang Selatan obtained the results of the T_count value> T_table or (10.946> 1.668) this is reinforced by the Sig value (0.000 <0.05). Thus, H_O is rejected and H_2 is accepted. So it can be stated partially that there is a significant positive influence on employee performance (Y) at PT Berkat Mahkota Putra Tangerang Selatan. The third hypothesis test, namely the influence of work motivation (X1) and workload (X2) on employee performance (Y) at PT Berkat Mahkota Putra Tangerang Selatan, obtained the F_count value> F_table or (98.718> 3.130), this is also reinforced by Sig (0.000 <0.05). Thus, H_O is rejected and H_3 is accepted. This means that simultaneously work motivation and work discipline have a significant effect on employee performance (Y) at PT Berkat Mahkota Putra Tangerang Selatan Keywords: Work Motivation, Work Discipline, Employee Performance